Pengaruh CEO Power, Good Corporate Governance, dan Struktur Kepemilikan Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Sinaga, Veronica Maghdalena; Wulandari, Putu Prima (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to determine the effect of CEO power, good corporate governance projected by the size of the board of commissioners and independent commissioners, and the ownership structure projected by foreign ownership and managerial ownership on Corporate Social Responsibility (CSR) disclosure. This study employs a quantitative explanatory approach involving all sectors of companies listed on the Indonesia Stock Exchange between 2020 and 2021 as the study object and includes 210 samples selected through purposive sampling, from which 420 data are collected and analyzed by multiple regression utilizing SPSS 26 software. The results exhibited that CEO power, independent board of commissioners, and foreign ownership had no effect on CSR disclosure whilst the size of the board of commissioners and managerial ownership had a positive effect on CSR disclosure. This indicates that the larger the size of the board of commissioners and the number of managerial owners in a company, the greater the CSR disclosure made.